Profile of users assisted at the Research and Extension Laboratory in Integrative and Complementary Health Practices (LAPPICS) - Perovano Remydio, Bruno; Dias Negreli, Júlia; Amorim Melgaço Guimarães do Bem, Daniela; Carla de Melo Rodrigues, Lívia; Cristina Nascimento Chiaradia, Ana; Kelly Filgueiras Freitas, Grace; Pinheiro Borges, Bárbara Juliana (Guará Journal, 2025)
The Laboratory for Research and Extension in Integrative and Complementary Practices in Health (LAPPICS) aims to develop research and extension with integrative practices, offering ear acupuncture and reiki services for people who have acute and chronic pain, and anxiety disorders. The aim of the work is to analyze the profile of patients treated at LAPPICS through a cross-sectional, analytical, quantitative, population-based study. 610 consultations were carried out in the years 2022 and 2023. The majority of laboratory participants were aged between 16 and 30, are female students and reside in greater Vitória. The main symptoms and complaints presented in the anamnesis carried out at the first consultation were “anxiety”, “depression”, “association between anxiety and depression”, “other psychological disorders”, “association between anxiety and pain” and “only pain”. It is important to know the profile of users of Integrative and Complementary Health Practices (PICS) at the university, so that strategies, research and campaigns can be developed in order to qualify the service, strengthen it, develop it as a care offer, extension activity and research field.
Keywords: Auriculotherapy; Extension project; Reiki; User profile